Duration of hospital admission, need of on-demand analgesia and other peri-procedural and short-term outcomes in sub-cutaneous vs. transvenous implantable cardioverter–defibrillators. (1st May 2018) - Boveda, Serge; Chalbia, Tej Elbanet; Jacob, Sophie; Combes, Stéphane; Combes, Nicolas; Cardin, Christelle; Laborie, Guillaume; Sousa, Maria Joao; Jebberi, Zeynab; Mzoughi, Sophia; Albenque, Jean-Paul; Providencia, Rui
Abstract: Background: Post-procedural recovery following sub-cutaneous ICD (S-ICD) implantation is feared to be more painful and to require more prolonged hospital admission. The purpose of this study was to compare peri-procedural and short clinical outcomes of the S-ICD vs. the Transvenous ICD (TV-ICD). Methods: We conducted a single-center cross-sectional study including all consecutive patients who underwent S-ICD implantation by the same operator since January 2016 and a gender and age-matched control group with all single chamber TV-ICD implanted patients over a contemporary time period. Results: Thirty-one patients (sex ratio 1/5; mean age 58.7 ± 13.2 years) with S-ICD were compared to 31 matched TV-ICD patients. Duration of the implant procedure was significantly longer for the S-ICD (58.0 ± 24.4 min vs 41.7 ± 20.8 min TV-ICD, p  < 0.01). Mean fluoroscopy time for the TV-ICD was 3.5 ± 3.6 min vs 0.1 ± 0.01 min for all S-ICD patients ( p  < 0.01). Requirement of on-demand analgesia administration, and duration of hospitalization (1.5 days for both groups; p  = NS) were similar in the two groups. No peri-procedural events were reported, and after a mean follow-up of 6 months, the only complication was a pocket infection requiring reintervention in the TV-ICD group. Conclusions: The S-ICD appears to be as effective and safe as the conventional single chamber TV-ICD. Duration of hospital admission and need of on-demand analgesia are also comparable for S-ICD patients.